Efecto de abonos orgánicos sobre la producción en el cultivo de plátano dominico (Musa spp.) en la zona de Valencia - Bermeo Aguilar, Kevin Enrique (2021)
Fertilizers are a natural product resulting from the disintegration of materials of animal, vegetable or sometimes mixed origin, with the ability to improve soil fertility. The main objective of this research was to evaluate the effect of organic fertilizers on production in the cultivation of Dominican plantain. This experiment was carried out on the farm of Mr. Manuel Bermeo Duran, located in Valencia canton, in an established 4-year-old plantation, the duration of the experiment was 4 months, due to the fact that the plants were monitored and selected. next to produce the acorn. Five fertilization treatments were evaluated that consisted of; fertilization with humus (T1), chicken manure (T2), Biol (T3), complete fertilizer control (T4) and absolute control without any type of fertilization (T5). The data obtained in the collection of results were subjected to an analysis of variance and the separation of means with the Tukey test at 5% probability of error, using the statistical program Infostat. The variables evaluated in this research were: bunch weight, finger grade, number of hands per bunch, finger length, percentage of damage by insects and percentage of loss. The results showed that the complete fertilizer control treatment showed the best yield in question to the production in the Dominican plantain crop, with a bunch weight of 28.55 kg, 8 hands per bunch and a finger grade of 46.45 inches, however, the other treatments that obtained lower yields in production, on the other hand, with regard to the percentage of damage by insects, the most attacked treatment was the absolute control with 11.7%. The humus in this investigation as organic fertilizer was not an effective source to increase the crop yield, since it was found in a low yield. The economic analysis showed that the highest net profit reached fell on the control treatment fertilized with complete manure with a value of 2,577.82. Keywords: compost, organic, fertilization, banana.